Pengaruh Media Baamboozle terhadap Motivasi Belajar Siswa Kelas VIII pada Mata Pelajaran PKn di SMP Negeri 7 Watampone - Mutiara Mutiara; Suhardiman Suhardiman; Ahmad Nurul Ihsan B (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the effect of Baamboozle media on the learning motivation of eighth-grade students in the Pancasila and Civic Education (PKn) subject at SMP Negeri 7 Watampone. The background of this study is the low level of students’ learning motivation in PKn learning, which is often perceived as less engaging. To overcome this problem, an interactive game-based learning medium, Baamboozle, was implemented to create a more enjoyable learning atmosphere and to increase students’ learning motivation. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The research sample consisted of two classes: an experimental class that used Baamboozle media and a control class that used conventional learning media. Data were collected through learning motivation questionnaires, observation, and documentation. The data were analyzed using statistical tests to test the research hypotheses with the assistance of the SPSS program. The results showed that the average learning motivation score of students in the experimental class increased from 55.62 in the pretest to 89.48 in the posttest, while the control class showed an increase from 54.62 to 74.74. The t-test results indicated a significance value (Sig. 2-tailed) of 0.000, which means there was a significant difference in learning motivation between the experimental and control classes. Therefore, it can be concluded that Baamboozle media has a positive and significant effect on students’ learning motivation in PKn learning.